AIDS with Disseminated Tuberculosis - Sanyal, Mousumi; Cader, F Aaysha; Amin, Muhammed Al; Das, Aparna; Kahhar, M Azizul (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) have been closely linked since the emergence of the Acquired Immune Deficiency Syndrome(AIDS). Worldwide, TB is the most common opportunistic infection affecting HIV-seropositive individuals,and it remains the most common cause of death in patients with AIDS. By producing a progressive decline in cell-mediated immunity, HIV alters the pathogenesis of TB, greatly increasing the risk of disease from TB in HIV-coinfected individuals, and leading to more frequent extrapulmonary involvement, atypical radiographic manifestations, and paucibacillary disease, which can impede timely diagnosis. Although HIV-related TB is both treatable and preventable, incidence continues to climb in developing nations, wherein HIV infection and TB are endemic and resources are limited. We report the case of a 45 year old gentleman who presented with generalized lymphadenopathy, whose lymphnode biopsy was consistent with TB; however following poor response to anti-TB treatment, he was found to be serologically positive for HIV. J Bangladesh Coll Phys Surg 2016; 34(3): 168-171